ADAPTASI BRAIN GYM BERBASIS MULTIMEDIA UNTUK KONSENTRASI ANAK TUNAGRAHITA - nFN Nurhayati (Kwangsan: Jurnal Teknologi Pendidikan, 2015)
A concentration is the most important factor in achieving the learning objectives.Children with intelectual disability encounter learning difficulties as they have intellectual sub normality which impact to their socially and mentally function, including the ability to concentrate. The omission of this problem can cause negative impact for the quality of life of children with intelectual disability. Therefore, a number of strategies to overcome this problem should be proposed. One of the useful solutions to help them is using the brain gym in the learning activities. This research aims to design an adaptation product of brain gym based on the multimedia approach that claim could improve the concentration ability among the childrenwith intelectual disability. The research design is developed basedon the Borg and Gall model (2003). This research result a video complete with the accompanying material. The video consists of 10 brain gym exercises which adapted from the brain gym introducedby Paul E. Denisson. The accompanying material is prepared to explain the brain gym exercises as demonstrated in the video. Based on the expert test and the field test, the product fulfils the goodness offit criteria. The result of expert test from the educational technology, the content (penjasorkes) and psychologist are 2,71; 2,75 and 2,68 respectively. Furthermore, the field test indicates the effectiveness of this product with the paired t-test is t = 3,433 > 1,833 and significance level equal to 0,05. In conclusion, the adaptation product of brain gym based on the multimedia approach can improve the concentration ability of children with intelectual disability. AbstrakSalah satu hal yang terpenting dalam mencapai tujuan belajar adalah konsentrasi. Bagi anak tunagrahita, aktivitas belajar memiliki hambatan karena anak tunagrahita mengalami subnormalitas dalam kecerdasan yang berdampak pada kemampuan fungsi sosial dan mentalnya termasuk konsentrasi. Hal ini jika dibiarkan akan berdampak negatif pada perkembangan kualitas hidup anak dikemudian hari. Berdasarkan hal tersebut perlu dicari solusi untuk mengatasinya, diantaranya adalah dengan menggunakan brain gym dalam kegiatan belajar mengajar. Penelitian ini bertujuan untuk mengembangkan produk adaptasi brain gym berbasis multimedia yang dapat meningkatkan konsentrasi anak tunagrahita. Rancangan penelitian pengembangan menggunakan model Borg and Gal (2003). Penelitian ini menghasilkan produk berupa video dan bahan penyertanya.Isi video berupa tutorial 10 gerakan brain gym yang diadaptasi dari brain gym ciptaan Paul E. Denisson. Bahan penyerta dibuat untuk memperjelas seluruh gerakan brain gym yang ada pada video. Produk pengembangan adaptasi brain gym berbasis multimedia dinyatakan layak untuk digunakan berdasarkan uji ahli dan uji lapangan. Rata-rata penilaian dari 3 orang ahli yaitu ahli desain instruksional dengan nilai 2,71, ahli materi (penjasorkes) dengan nilai 2,75 dan psikolog dengan nilai 2,68. Hasil uji lapangan menunjukkan keefektifan produk adaptasi brain gym berdasarkan perhi tungan uji t dengan nilai t = 3,433 > 1,833 taraf signifikan 0,05. Kesimpulan penelitian pengembangan menunjukkan bahwa produk adaptasi brain gym berbasis multimedia dapat meningkatkan kemampuan konsentrasi anak tunagrahita.